Ultra-sensitive triethylamine sensors based on oxygen vacancy-enriched ZnO/SnO2 micro-camellia - Yong-Hui, Zhang; Wang, Chao-Nan; Fei-Long, Gong; Jun-Li, Chen; Ke-Feng, Xie; Hao-Li, Zhang; Shao-Ming, Fang (Journal of materials chemistry. C, Materials for optical and electronic devices, 2021)
The detection of volatile organic gas triethylamine (TEA) is of great significance to environment quality and human health. However, it is still a challenge to achieve high-sensitivity detection at low temperatures. In this work, a TEA sensor with a low operating temperature and high response was successfully prepared by designing ZnO/SnO2 composite material rich in oxygen vacancy defects. A camellia-like ZnO material was synthesized by a hydrothermal method using surfactant, bis(2-ethylhexyl)sulfosuccinate sodium salt (AOT) as a soft template. SnO2 nanoparticles with a diameter of 20 nm were dispersed on ZnO nanosheets to form a ZnO/SnO2 heterostructure. The sensor based on ZnO/SnO2-10 demonstrates an extremely high response of 780 to 100 ppm TEA. More importantly, the response value of 1 ppm TEA detected is 6 and the detection limit is as low as 0.43 ppm. Besides, the sensor has a low working temperature of 100 °C. The enhancement of TEA sensing performance could be attributed to the synergistic effect of oxygen vacancy (Vo), ZnO–SnO2 heterojunction, and the ZnO (001) exposure plane. Vo can be used as the active center of oxygen molecule adsorption to produce highly active O2− species. Furthermore, Vo–ZnO has higher adsorption energy for TEA molecules than pure ZnO, which was determined using first-principles calculations, confirming the strong interaction between Vo–ZnO and TEA. The sensor shows a broad application prospect in food safety detection and environmental monitoring.